Magnetic and Mossbauer spectroscopic studies of NiZn ferrite nanoparticles synthesized by a combustion method - Sreeja, V.; Vijayanand, S.; Deka, Sasanka; Joy, Pattayil Alias (Hyperfine Interactions, 2008)
The properties of nanocrystalline Ni(0.5)Zn(0.5)Fe(2)O(4) synthesized by an auto-combustion method have been investigated by magnetic measurements and Mossbauer spectroscopy. The as-synthesized single phase nanosized ferrite powder is annealed at different temperatures in the range 673-1,273 K to obtain nanoparticles of different sizes. The powders are characterized by powder X-ray diffraction, vibrating sample magnetometer, transmission electron microscopy and Mossbauer spectroscopy. The as-synthesized powder with average particle size of similar to 9 nm is superparamagnetic. Magnetic transition temperature increases up to 665 K for the nanosized powder as compared to the transition temperature of 548 K for the bulk ferrite. This has been confirmed as due to the abnormal cation distribution, as evidenced from room temperature Mossbauer spectroscopic studies.
Keywords: Ferrite; magnetic properties; Mossbauer spectroscopy; Nanoparticles

Size dependent coordination behavior and cation distribution in MgAl2O4 nanoparticles from Al-27 solid state NMR studies - Sreeja, V.; Smitha, T. S.; Nand, Deepak; Ajithkumar, Thalasseril G.; Joy, Pattayil Alias (Journal of Physical Chemistry C, 2008)
Nanoparticles of spinel-type oxides such as ferrites offer great advantages and applications in many important areas. Decreasing the size of the particles to nanometer size will increase the surface-to-volume ratio and this will strongly influence the physical and chemical properties of these materials. For magnetic nanoparticles, the exchange interactions at the surface of a particle will be different from those inside due to changes in the coordination behavior at the surface. Therefore, studying and understanding the coordination and distribution behavior of the different metal ions in the nanoparticles of spinel-type oxides is very important. Solid state NMR is a useful and important technique to obtain information on local structural variations. The degree of the distribution of the Al3+ ions in the tetrahedral and octahedral sites in the nanoparticles of the nonmagnetic spinet MgAl2O4 having different particle sizes has been determined by Al-27 magic-angle spinning (MAS) NMR spectroscopy. It has been observed that the inversion parameter decreases with increasing particle size. Apart from the usual tetrahedral and octahedral coordinations present in the bulk material, the presence of five- and three-coordinated At has been observed in nanoparticles with sizes less than 18 nm and a second octahedral coordination is observed for nanoparticles of larger sizes.

Rapid generation of hierarchical nanoarchitectures of CdS via facile microwave assisted hydrothermal/semi-solvothermal route - Shinde, Manish D.; Pawar, Amol U.; Sreeja, V.; Rane, Sunit; Potdar, Hari S.; Amalnerkar, Dinesh P. (International Journal of Nanotechnology, 2010)
1-D nanorod bundles as well as sea urchin and starfish like hierarchical morphological nanoarchitectures of CdS have been synthesised using a facile microwave assisted hydrothermal/semi-solvothermal technique. Observation of interesting regular/irregular pine-tree like secondary growth over these hierarchical nanoarchitectures is an important aspect of this work. Cadmium acetate and thiourea were used as precursor materials and were dissolved in solution containing mixture of diethylene triamine (DETA) and deionised water (DIW) in different volume ratios prior to subjecting the resultant solution to microwave radiation of 300 W at a reaction time of 10 min and temperature of 140 degrees C. XRD revealed formation of hexagonal CdS with strong (002) preferred orientation (c-axis orientation). Morphology dependent optical properties are studied using room temperature photoluminescence spectroscopy. We feel such secondary growth will be highly favourable in determining the non-linear properties of optoelectronic devices fabricated using such novel hierarchical nanoarchitectures.
Keywords: CdS; hierarchical nanoarchitectures; Microwave; Nanorods; secondary growth; solvothermal synthesis

Effect of inter-particle interactions on the magnetic properties of magnetite nanoparticles after coating with dextran - Sreeja, V.; Joy, Pattayil Alias (International Journal of Nanotechnology, 2011)
Nanoparticles of magnetite (Fe3O4) are synthesised by a coprecipitation method and coated with the biocompatible polymer, dextran. The uncoated and dextran coated magnetite nanoparticles are characterised by powder X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and magnetic measurements. The magnetic properties of the uncoated and coated magnetite nanoparticles are compared to study the effect of inter-particle magnetic interactions on the magnetic characteristics. Absence of magnetic hysteresis at room temperature indicates the superparamagnetic nature of the two samples. Evidence for the effect of reduced inter-particle magnetic interactions is directly obtained from the field dependence of magnetisation at room temperature. The decreased superparamagnetic blocking temperature and the nature and shape of the field cooled magnetisation curve of the dextran coated sample further confirmed that the inter-particle magnetic interactions are completely suppressed after coating.
Keywords: dextran coating; magnetic interactions; magnetic properties; magnetite; Nanoparticles

Water-dispersible ascorbic-acid-coated magnetite nanoparticles for contrast enhancement in MRI - Sreeja, V.; Jayaprabha, Kunnoth N.; Joy, Pattayil Alias (Applied Nanoscience, 2015)